4x-9=-6+5x

Simple and best practice solution for 4x-9=-6+5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-9=-6+5x equation:


Simplifying
4x + -9 = -6 + 5x

Reorder the terms:
-9 + 4x = -6 + 5x

Solving
-9 + 4x = -6 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-9 + 4x + -5x = -6 + 5x + -5x

Combine like terms: 4x + -5x = -1x
-9 + -1x = -6 + 5x + -5x

Combine like terms: 5x + -5x = 0
-9 + -1x = -6 + 0
-9 + -1x = -6

Add '9' to each side of the equation.
-9 + 9 + -1x = -6 + 9

Combine like terms: -9 + 9 = 0
0 + -1x = -6 + 9
-1x = -6 + 9

Combine like terms: -6 + 9 = 3
-1x = 3

Divide each side by '-1'.
x = -3

Simplifying
x = -3

See similar equations:

| -4.9t^2+24.5t+2=0 | | 7x+3x-4x=3-3(x+4) | | 139=-5-2(4+8P) | | (5x^3y^2-3xy^5+12x^2)-(-9x^2-8x^3y^2+2xy^5)=0 | | 4x-9=-6+-5x | | 3x(-3)+b= | | 7-3a=11+a | | X(15x+11x)+2=0 | | 4.9t^2-24.5t+2=0 | | c^2-3c-18= | | 6+3(13-2)-25= | | 5x+2-4x=5+8 | | -5y+7y=10 | | 2(4p+3)-3(3p-6)-16p= | | -6(7x-1)=-8x+9(-3x+4) | | .5(4m+5)=-6 | | t^2-24.5t+2=0 | | 2a/3a-3/4=3a/4a | | h(t)=-16t^2+20t+4 | | 7+3a=11-a | | 3(4x-6)=2(4x-3)-(x+8) | | 13.04=f+8.25 | | 9n-3n= | | 13(t+1)-3(2+4t)=48 | | 180=(9x+4)-y | | -15=-5t^2+30t | | 9-3x+5x=-11 | | 2-(x+3)=6 | | 5x+4=37 | | X^2+6x-34=0 | | y+x=y-x | | 2(x-5)+2x=x+3x-2x |

Equations solver categories